Meningkatkan Aksesibilitas dan Personalisasi dalam Pembelajaran Jarak Jauh melalui Teknologi E-Learning Adaptif - Setiawati, Eka; Edwards, John; Siahaan, Mungkap Mangapul (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2025)
The global shift towards digital education accelerated by the COVID-19 pandemic has revealed ongoing challenges in ensuring equitable access and personalized learning experiences among diverse student populations. This study aims to investigate the potential of adaptive e-learning technology in enhancing accessibility and individualization within the context of distance education, particularly for students from marginalized communities and remote geographical areas. By employing a mixed-methods approach, this research involved a survey of 312 students from various demographic backgrounds, as well as in-depth case studies at two institutions that have implemented adaptive learning systems. The findings indicate that students using adaptive platforms experienced significant improvements in learning engagement, with 74% reporting better understanding and 61% noting increased motivation compared to their peers using conventional online learning methods. The adaptive systems also demonstrated the ability to tailor content based on the pace, preferences, and prior knowledge of learners, effectively narrowing achievement gaps. Furthermore, accessibility features such as language customization, device compatibility, and offline usability proved crucial in supporting inclusivity. This study concludes that the integration of adaptive e-learning technology in distance education can play a transformative role in addressing educational disparities by aligning instruction with the unique needs of learners while expanding access to quality digital education. These findings hold significant value for policymakers, educational technologists, and institutions seeking sustainable and inclusive strategies that align with the United Nations Sustainable Development Goal 4.